Detection of coronary microembolisation by Doppler ultrasound during percutaneous coronary interventions. Issue 9 (15th August 2005) - Bahrmann, P; Figulla, H R; Wagner, M; Ferrari, M; Voss, A; Werner, G S
Abstract : Objective: To validate an intracoronary Doppler ultrasound device for high intensity transient signals (HITS) detection and to assess the incidence of HITS during percutaneous coronary intervention (PCI). Methods and Results: In an in vitro model, particle count and number of HITS detected by an intracoronary 0.014 inch Doppler wire were closely correlated ( r  =  0.97, p < 0.001). In the clinical study, 32 patients (mean (SD) age 61 (11) years; 23 men, nine women) with coronary artery disease were treated with balloon dilatation and stent implantation for a single vessel stenosis. In these patients HITS were detected during PCI in 84% (27 of 32). Reproducibility ( r  =  0.99, p < 0.001) and interobserver agreement ( r  =  0.84, p < 0.001) of HITS counts were significant. The number of HITS after stent implantation was significantly higher than after balloon dilatation (11 (7) v 2 (4), p < 0.001). Postprocedural coronary flow velocity reserve (CFVR) was < 2.0 in 55% (16 of 29) of all patients after balloon dilatation and < 2.0 in 23% (six of 26) after stent implantation. The number of HITS after stent implantation did not differ significantly between patients with CFVR < 2.0 and patients with CFVR ⩾ 2.0 (12 (8) v 10 (7), not significant). Conclusions: Embolic particles can be detected as HITS by an intracoronary Doppler ultrasound device. Coronary microembolism is often observed during PCI, especially after stent implantation. However, the incidence of HITS alone does not explain a reduced CFVR after PCI.